Noroviruses and sapoviruses associated with acute gastroenteritis in pediatric patients in Thailand: increased detection of recombinant norovirus GII.P16/GII.13 strains - Pattara Khamrin (2018)
© 2017, Springer-Verlag GmbH Austria. Enteric caliciviruses, including noroviruses (NoVs) and sapoviruses (SaVs), are recognized as important etiologic agents of acute gastroenteritis (AGE) with considerable genetic diversity. In order to gain an overview of the molecular epidemiology of human NoVs and SaVs in children hospitalized with AGE in Chiang Mai, Thailand, a total of 889 fecal specimens were collected from 2012 to 2014 and screened for NoVs and SaVs. Out of 889 fecal specimens, 154 (17.3%) and 6 (0.7%) were positive for NoV GII isolates and SaV, respectively. Among the NoV GII, 10 different genotypes were identified with genotype GII.4 being predominant (103 strains), followed by GII.3 (17 strains), GII.13 (13 strains), GII.1 (7 strains), GII.6 (7 strains), GII.7 (2 strains), GII.17 (2 strains), and one each of GII.2, GII.15, and GII.21 genotypes. It was observed that four variants of NoV GII.4 (Den Haag 2006b, Apeldoorn 2007, New Orleans 2009, Sydney 2012) were detected from 2012 to 2014. Analysis of partial nucleotide sequences of RdRp and VP1 of the emerging NoV GII.13 strains (9 of 13 strains) revealed that they all were GII.P16/GII.13 recombinants. In addition, four different genotypes of SaV, GI.1 (2 strains), GII.1 (1 strain), GII.4 (2 strains), and GIV.1 (1 strain) were detected. The data revealed heterogeneity and a highly dynamic distribution of NoV and SaV genotypes circulating in children admitted to hospitals with AGE in Chiang Mai, Thailand, during the period of 2012 to 2014.